Intrapersonal Communication as the Foundation of Public Speaking for Gen-Z Employees: A Case Study at New Cammary Cafe - Yuan Khoir; Farabi Avicena Zulkarnain (Journal of Citizenship, 2025)
This study aims to analyze the role of intrap communication as a foundation in the formation of public speaking skills among Generation Z employees at New Cammary Cafe, Bandung. Generation Z, who grew up in the digital era, has unique communication characteristics, especially in face-to-face interactions that require confidence, emotional management, and spontaneity in speaking. This study uses a qualitative approach with a case study method to explore in depth the subjective experiences of employees in managing intrapersonal communication and its implications for public communication performance. Data were obtained through in-depth interviews with four employees consisting of baristas and waitresses, as well as direct observation of service activities and communication interactions in the work environment. The results show that intrapersonal communication plays an important role in shaping employees' mental and emotional readiness when dealing with customers. The dominant forms of intrapersonal communication include positive self-talk, self-reflection, and social imagination, which serve as mechanisms for managing anxiety and strengthening self-confidence. Healthy intrapersonal communication has been proven to support employees public speaking abilities, particularly in explaining products, responding to customer questions, and handling challenging communication situations. In addition, the existence of informal discussion spaces such as SAMARA activities helps strengthen public speaking skills while enriching the personal reflection process of employees. This study concludes that the development of public speaking skills cannot be separated from the strengthening of intrapersonal communication. Therefore, communication training in the informal service sector needs to adopt a holistic approach that focuses not only on speaking techniques but also on self-awareness, emotion management, and personal reflection, especially for Generation Z employees. Keywords: intrapersonal communication, public speaking, Generation Z, cafes, case study